On the behavior of entrepreneurial factor supply to the firm - Nicos Zafiris (The Journal of Entrepreneurial Finance (JEF), 2016)
This paper draws on an existing, but little used, approach to the choices governing the supply of 'entrepreneurial', in the sense of 'residually remunerated', resources to an enterprise, especially post start up. It focuses in particular on the hybrid 'own factor demand/supply curve' to the firm of Bronfenbrenner (1960), but attempts to treat such supply in conjunction with 'contractual' employment of resources, thus making use of gearing and portfolio concepts. To achieve this, it is found necessary for the hybrid schedule to be reinterpreted and recast as the locus of the relevant utility maximising choices. A model is presented which features combining all productive resources in a single factor F so as to concentrate on the choice between the entrepreneurial and contractual employment of these. The model identifies a variety of possible entrepreneurial resource supply responses to product market signals, including the possibility of divergence from the 'normal' expectation of a monotonically upward sloping supply curve. Such 'unexpected' behaviour is seen as rational and consistent, both with the needs of survival in distress and of safeguarding gains in the upside. Hence it is also efficient on welfare grounds. Analogies with the backward bending labour supply model and with risk/return choices in finance are pursued. The policy implication is that greater use of equity, especially in start ups and distress situations, should be encouraged.
Keywords: D01; D21; G32; 650; Entrepreneurial; Factor Supply; Utility; Gearing; Backward Bend